Karya Al Tawabi’ wa Al Zawabi’ oleh Ibn Shuhayd dan Risalat Al Ghufran oleh Al Ma’ari: satu adaptasi daripada peristiwa Isra’ Mi’raj” (Ibn Shuhayd’s Al Tawabi’ and Al Ma’ari’s Risalat Al Ghufran: an adaptation of the Isra’ Mi’raj incident). - Ahmad H.Osman, Rahmah; Nasir, Mohd Shahrizal (Surakarta State Islamic College (STAIN Surakarta), 2010)
Fourteen hundred years ago al-Isra’ wa al-Mi‘raj or ‘The Night Journey’ brought to the world something that changed the course of history. The Isra’ Mi‘raj is considered a sign of Allah’s power by the God conscious. Therefore, this magnificent journey which contains a thousand and one wisdoms and miracles is very significant in Islam and will remain etched in the history of Islam. This article discusses the impact of the Isra’ Mi‘raj in the world of Arabic literature. For this purpose, this study will analyses two examples of Arabic literary works, which have been directly or indirectly inspired by the Isra’ Mi‘raj: al-Tawabi‘ wa al-Zawabi‘ and Risalat al-Ghufran. This article unveils a number of issues, which are seen as a direct result from the impact of the Isra’ Mi‘raj. Should this aspect really exist in these literary works, an inevitable fact avails, which is, that the Isra’ Mi‘raj has definitely played a significant role in fiction writings of Arabic literatures. Having established the above, caution should be practiced to ensure that the truth behind the Isra’ Mi‘raj be preserved and protected from any negative and offensive elements towards Islam and Muslims, notwithstanding the artistic nature of the works in scrutiny. Without any doubt, Isra’ Mi‘raj is a fact that has been mentioned in the Qur’an and the authentic Hadith of the Prophet Muhammad SAW.